(untitled) (International Journal of Petroleum Technology, 2021)
Ni-cermet anode demonstrates excellent catalytic activity and electrical conductivity but suffers from carbon deposition issue. To utilize Ni-cermet anode while preventing carbon deposition, a synergic strategy is employed to design anode electrode. In particular, Zr is incorporated into Ce0.8Sm0.2O2-δ lattice to tailor oxygen storage and catalytic properties of Ni-Ce0.8-xSm0.2ZrxO2-δ anode for improving electrochemical oxidizations of various fuel species. An inert thick YSZ microtubular substrate with radially well-aligned microchannels open at the inner surface is used to support multi thin functional layers of solid oxide cell, i.e., Ni current collector, Ni-Ce0.8-xSm0.2ZrxO2-δ anode, YSZ/SDC electrolyte, and LSCF cathode. The thick YSZ substrate is able to inhibit the ratio of fuel to product gases in the thin anode functional layer, which favors the prevention of carbon buildup in the thin anode layer when synergistically combined with Ni-Ce0.8-xSm0.2ZrxO2-δ anode material. The microchannels embedded in the YSZ substrate can also avoid too much dilutions of the fuel in the anode functional layer. The cell is fabricated and tested with both hydrogen and methane as the fuel. A short-term test is conducted with methane as fuel and good stability is obtained. The fundamental mechanisms for the prevention of carbon buildup in anode functional layer are also discussed.